PENGARUH RASIO KEUANGAN, ECONOMIC VALUE ADDED, DAN MARKET VALUE ADDED TERHADAP HARGA SAHAM PERUSAHAAN TERINDEKS PEFINDO 25 - Dheni Indra Kusuma (Sekolah Tinggi Ilmu Ekonomi Widya Wiwaha, 2018)
The capital market has been progressing very rapidly. The annual financial statements of companies listed on the Indonesia Stock Exchange have become one of the investor analysis tools to take a business action. The decision of the investor will affect the value of the company reflected through the stock market price of the company. Financial ratios are still trusted by investors as the basis for analysis in decision making. Methods of Economic Value Added, and Market Value Added emerged as an alternative complement information for investors to analyze and make decisions.This study aims to examine the influence of financial ratios, Economic Value Added, and Market Value Added on stock prices. The sample to be observed are companies that are included in the index PEFINDO 25. The growing of beginner investors and Small and Medium Enterprises that entered the Indonesia Stock Exchange became the basis of interest researchers to conduct this research. Hypothesis testing was performed by using crosssectional regression for each year observation from 2010-2015 and all pooled regression years. This study uses observational company data selected by purposive sampling year 2010-2015 from all companies listed in Indonesia Stock Exchange included in index PEFINDO 25. The results shows that variables of DER, PER, EVA, and MVA affects in the companies.